CATEGORY OF BALANCE IN THE MANAGEMENT OF INDUSTRIAL ENTERPRISES - Pavel Timoshenko (Вестник Северо-Кавказского федерального университета)
The problems of the term use of the balance of the in the industry control system. Analyzed the specifics of the term balance in management, economics and finance. Given the generalizing definition of balance.